Wealth Distribution within Couples - Markus M. Grabka; Jan Marcus; Eva Sierminska (Institute for the Study of Labor (IZA), 2013)
While most studies on wealth inequality focus on the inequality between households, this paper examines the distribution of wealth within couples. For this purpose, we make use of unique individual level micro data from the German Socio-Economic Panel Study (SOEP). In married and cohabiting couples men's net worth, on average, is 33,000 euros higher than women's. We look at five different sets of factors (demographics, income, labor market, inheritances, financial decision-making in the partnership) that might explain this wealth gap. We find that all factors contribute to the explanation of the wealth gap within partnerships, with inheritances and income being particularly relevant. Furthermore, we find that specific characteristics (e.g., self-employment, no migration background, inheritances, high income) that decrease the wealth gap for women increase it for men. For men the respective coefficients are even stronger in absolute terms. When examining intra-partnership financial decision-making, we find the gap to be significantly smaller when the female partner manages the money and larger if the male partner has the last word in financial decisions.
Keywords: J2; D13; D31; D69; I31; 330; intra-household allocation; wealth inequality; wealth gap; gender; financial decision-making; SOEP